Pemanfaatan Teknologi Digital Upaya Meningkatkan Literasi Digital dan Motivasi Membaca Siswa Sekolah Dasar - Julistin Prilianis Dakhi; Adelia Febrianti; Risking Waruwu (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
In today's digital era, technology plays a crucial role in supporting innovative, interactive, and engaging learning processes. Education is no longer limited to the use of conventional textbooks and whiteboards, but has been transformed through the integration of various digital media. In this context, digital literacy has become a key competency that students must possess. Digital literacy encompasses not only the ability to access and understand information from various digital sources but also involves critical thinking and collaborative skills, as well as the wise, ethical, and responsible use of technology. Studies show that the appropriate and targeted use of digital media can increase students' interest in reading materials and other learning activities. Interactive and visually appealing digital media can stimulate students' curiosity, enrich the learning experience, and increase their motivation. Furthermore, the use of digital technology also provides opportunities to develop creativity, communication skills, and problem-solving skills. Technology-based learning enables more effective learning differentiation, allowing students to learn at their own pace and learning style. This is highly relevant in the context of 21st-century education, which demands information literacy, technology literacy, and media literacy. As learning facilitators, teachers are required not only to be proficient in using technology but also to design learning that integrates curriculum content with available digital potential. Therefore, optimal use of digital technology can be a strategic solution in creating a generation that is digitally literate, creative, innovative, and able to adapt to increasingly dynamic and complex developments. To achieve this goal, collaboration between schools, the government, and parents is essential in providing adequate access to and training in sustainable educational technology.